The efficacy and safety of epidural morphine/hydromorphone in the treatment of intractable postherpetic neuralgia: A single-center, double-blinded, randomized controlled, prospective, and non-inferiority study - Yiping, Sun; Jiayi, Shen; Guang, Hei; Yun, Ji; Bingjie, Ma; Xuehua, Huang; Zhiyuan, Yu; Pingchuan, Ma; Ke, Ma (Frontiers in Pharmacology, 2022)
Objective: Postherpetic neuralgia (PHN) is a clinical puzzle, especially in patients who still suffered from moderate and severe pain after standard treatment. This single-center, double-blinded, randomized controlled, prospective, and non-inferiority study observed the safety and effectiveness of the epidural application of morphine or hydromorphone, trying to provide an alternative method for those patients with refractory PHN. Methods: Eighty PHN patients with a visual analogue scale (VAS) still greater than 50 mm after routine management were randomly divided into two groups according to 1:1, respectively. One group received epidural morphine (EMO group), and the other group received epidural hydromorphone (EHM group). VAS, the number of breakthrough pain, quality of life (QOL), and anxiety/depression assessment (GAD-7 and PHQ-9 scores) were also observed before treatment, at 1, 3, 7, 14, 21, 28, 60, and 90 days after treatment, as well as side effects. Opioid withdrawal symptoms (OWSs) were also measured from 3 to 28 days after treatment. Results: The EHM group was non-inferior to the EMO group in terms of the VAS decrease relative to baseline (VDRB) after 1-week treatment. The VAS of the two groups on all days after treatment was significantly lower than the corresponding baseline findings (p < 0.05). The breakthrough pain (BTP) decreased significantly after treatment and lasted until 14 days after treatment (p < 0.05). There was no significant difference in BTP between the two groups at each time point (p > 0.05). In terms of the QOL, GAD-7, and PHQ-9 outcomes, those were significantly improved after treatment (p < 0.05), and there was no difference between the two groups (p > 0.05). No significant AE difference across the two groups was observed in this study. Few reports of OWS were found in this trial, and there were no significant differences between the two groups (p > 0.05). Conclusion: EHM was non-inferior to EMO in terms of the VDRB after 1-week treatment. For patients with VAS still greater than 50 mm after standard treatment, short-term application of EMO or EHM can ameliorate intractable pain, improve the quality of life, and have no obvious side effects. Short-term epidural opioid application will not lead to the appearance of OWS.